NOX2 single nucleotide polymorphisms may impact on progression of multiple sclerosis - Törnell, Andreas (My University, 2020)
Multiple sclerosis (MS) is a neurodegenerative disease of the central nervous system (CNS) where the main pathogenesis is myelin damage that affects nerve cell signaling with ensuing physical and cognitive disabilities. Reactive oxygen species (ROS) and redox imbalances have been implicated in MS, where oxidized lipids and DNA in active lesions are co-localized with activated microglia capable of producing ROS. Most patients first experience a period of relapsing remitting MS (RRMS) from disease onset and then progress to secondary progressive MS (SPMS), although some have primary progressive MS (PPMS) with progressive disease from onset. However, there is considerable variation in the severity of symptoms and the rate of disease progression between patients. We aimed to investigate if single nucleotide polymorphisms (SNPs) in CybA, which encodes the subunit CYBA/p22phox of the ROS-producing myeloid NADPH oxidase 2 (NOX2), may impact on NOX2 derived ROS formation from myeloid cells and on clinical parameters in MS patients. Previous studies suggest that genetic variation at rs4673 and rs1049254 within CybA affects NOX2-derived ROS formation. Hence, myeloid cells from carriers of rs4673 minor allele A and rs1049254 major allele G were reported to produce reduced levels of ROS upon stimulation. Patient samples from two MS cohorts and peripheral blood mononuclear cells (PBMCs) from healthy donors were genotyped for the SNPs rs4673 and rs1049254. The healthy donor PBMCs were stimulated with fMLF and WKYMVm (L-peptide) to induce NOX2-derived production of ROS (”respiratory burst”), which was recorded using chemiluminescence. The magnitude of the respiratory burst was then correlated to CybA SNP genotypes. In agreement with previous studies, PBMCs from healthy subjects with rs4673 minor allele A and rs1049254 major allele G tended to produce lower levels of ROS upon stimulation (p=0.08; fMLF; rs1049254, p=0.2; L-peptide; rs4673). For the MS patients, the CybA SNP genotypes were correlated to MS disease severity using the Multiple Sclerosis Severity Score (MSSS) in the first cohort, which is based on an established neurological disability scale adjusted to present disease duration. In the second cohort, Regional Functional Scoring System (RFSS) was used, which is a detailed score measuring disability in seven anatomical regions but does not adjust the score to present disease duration. MS patients with either of the low ROS alleles showed significantly lower MSSS (p=0.024, rs4673 and p=0.018, rs104925). Patients with low ROS alleles in the second cohort tended to have a lower RFSS (p=0.1, rs4673 and p=0.09, rs1049254). When combining the cohorts and excluding patients who enter progressive disease within a year from onset and therefore may have primary progressive disease, patients with SNPs conferring low ROS production showed a significantly longer progression free survival (p=0.0068, rs4673 and p=0.0045 rs1049254). Statistical analysis was performed using linear and logistic regression as well as log-rank test for trend. Our results regarding the effects of genetic variation within the NOX2 subunit CYBA on NOX2-derived ROS formation are in line with previous studies. The finding that MS patients with the low-ROS genotypes rs4673 minor allele A and rs1049254 major allele G show reduced disease severity and longer PFS suggest that ROS-forming microglia and CNS-infiltrating macrophages may contribute to myelin damage and MS pathogenesis.